(untitled) (Revista Electrónica REDINE, 2024)
The intention of this essay focuses on rethinking the teaching practice mediated by technologies at the Barquisimeto Pedagogical Institute and aims to generate reflections on the didactic and curricular work of the teacher conceived as a Being that manages and transforms the teaching practice through the integration of Information and Communication Technologies (ICT) from the curricular dimension. Learning and teaching with (ICT) as mediating instruments in knowledge management processes (production, promotion, dissemination and dissemination of new knowledge), requires continuous reflection on academic and curricular processes, this leads to thinking about how is carrying out teaching activities within the university. Finally, teaching practice within the framework of virtual training processes must be assumed as a process oriented from the rationality of the teacher as an educational subject, which assumes the articulation between the conception of education, the curriculum, and technologies as key elements. , specific to the teacher, on which the institution needs to work to make adjustments and transformations, this in order to guarantee academic training that allows achieving the pre-established competencies in the curricular design and that is consistent with current educational demands.